2011
DOI: 10.1007/s10854-011-0555-y
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature sintering and microwave dielectric properties of zinc silicate ceramics

Abstract: Effects of ZnO-B 2 O 3 -SiO 2 glass on the sintering behavior, the microstructure, and the microwave dielectric properties of Zn 2 SiO 4 ceramics have been investigated. The ZnO-B 2 O 3 -SiO 2 glass lowered the sintering temperature of Zn 2 SiO 4 ceramics effectively from 1300 to 900°C. The X-ray diffraction results showed that the secondary phase of SiO 2 in the Zn 2 SiO 4 ceramics could be dissolved in the glass. The dielectric constant decreased slightly, and the quality factor decreased with increasing gla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…B 2 O 3 was served for reducing the sintering temperature of the CaMgSi 2 O 6 ceramics by Wang et al However, the sintering temperature of the CaMgSi 2 O 6 ceramics just reduced to 1100°C. Moreover, the free‐B 2 O 3 has inferior chemical compatibility with the organics in the technological process of LTCC . A low melting glasses were also considered as sintering aids to reduce the sintering temperature of CaMgSi 2 O 6 ceramics .…”
Section: Introductionmentioning
confidence: 99%
“…B 2 O 3 was served for reducing the sintering temperature of the CaMgSi 2 O 6 ceramics by Wang et al However, the sintering temperature of the CaMgSi 2 O 6 ceramics just reduced to 1100°C. Moreover, the free‐B 2 O 3 has inferior chemical compatibility with the organics in the technological process of LTCC . A low melting glasses were also considered as sintering aids to reduce the sintering temperature of CaMgSi 2 O 6 ceramics .…”
Section: Introductionmentioning
confidence: 99%
“…Diffraction peaks of ZnO or SiO 2 reported to be produced as the secondary phases in calcined powders or sintered specimens of Zn 2 SiO 4 were not observed. 13,15) While diffraction peaks of the secondary phase were not observed in the composition of x = 0.02 ( Fig. 1(a) and petalite (n = 8, LiAlSi 4 O 10 ), 17,18) where LiAlSi 3 O 8 is reported as the solid solution of β-LiAlSi 2 O 6 .…”
Section: Resultsmentioning
confidence: 94%
“…to enable co-firing of Zn 2 SiO 4 with metal electrodes. [6][7][8][9][10][11][12][13] Kim et al have reported a study where sintering temperature of Zn 1.8 SiO 3.8 was lowered to 900 o C in a composition with doping of 25.0 mol% B 2 O 3 while maintaining excellent microwave dielectric properties. 11) However, Li et al have reported in a study on water-system tape casting that viscosities of slurry were drastically increased with contents of B 2 O 3 doped to lower sintering temperature of the ceramics based on Li 2 O-Nb 2 O 5 -TiO 2 , which was attributed to the fact that B(OH) 4…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Table 1, the addition of various sintering aids allows to lower the sintering temperature of zinc orthosilicate based ceramics [6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%